Ribociclib plus letrozole in early breast cancer: A presurgical, window-of-opportunity study. (August 2016) - Curigliano, G.; Gómez Pardo, P.; Meric-Bernstam, F.; Conte, P.; Lolkema, M.P.; Beck, J.T.; Bardia, A.; Martínez García, M.; Penault-Llorca, F.; Dhuria, S.; Tang, Z.; Solovieff, N.; et al.
Abstract: Objectives: Cyclin D–cyclin-dependent kinase (CDK) 4/6–inhibitor of CDK4/6–retinoblastoma (Rb) pathway hyperactivation is associated with hormone receptor-positive (HR+) breast cancer (BC). This study assessed the biological activity of ribociclib (LEE011; CDK4/6 inhibitor) plus letrozole compared with single-agent letrozole in the presurgical setting. Materials and methods: Postmenopausal women ( N = 14) with resectable, HR+, human epidermal growth factor receptor 2-negative (HER2–) early BC were randomized 1:1:1 to receive 2.5 mg/day letrozole alone (Arm 1), or with 400 or 600 mg/day ribociclib (Arm 2 or 3). Circulating tumor DNA and tumor biopsies were collected at baseline and, following 14 days of treatment, prior to or during surgery. The primary objective was to assess antiproliferative response per Ki67 levels in Arms 2 and 3 compared with Arm 1. Additional assessments included safety, pharmacokinetics, and genetic profiling. Results: Mean decreases in the Ki67-positive cell fraction from baseline were: Arm 1 69% (range 38–100%; n = 2), Arm 2 96% (range 78–100%; n = 6), Arm 3 92% (range 75–100%; n = 3). Decreased phosphorylated Rb levels and CDK4, CDK6, CCND2, CCND3, and CCNE1 gene expression were observed following ribociclib treatment. Ribociclib and letrozole pharmacokinetic parameters were consistent with single-agent data. The ribociclib plus letrozole combination was well tolerated, with no Grade 3/4 adverse events over the treatment. Conclusion: The results suggest absence of a drug–drug interaction between ribociclib and letrozole and indicate ribociclib plus letrozole may reduce Ki67 expression in HR+, HER2– BC (NCT01919229). Highlights: This trial provides analysis of the biological activity of ribociclib + letrozole. Ribociclib + letrozole was well tolerated over a 2-week treatment period. Pharmacokinetic data suggest no ribociclib–letrozole drug interaction. Reduced Ki67 expression is reported in patients with HR+, HER2– breast cancer. Pharmacodynamic data provide evidence for on-target inhibition by ribociclib.